RUTA CHALEPENSIS LEAF EXTRACT'S PROTECTS METABOLIC INDICES ABNORMALITIES, TYPE 2 DIABETES, AND VARIOUS ORGANS TOXICITIES IN OBESE RAT - Ferjeni Zouidi (Chelonian Research Foundation, 2024)
Plant phenolics have been used as food supplements due to their capacity to prevent several ailments. Aim:The effects of Ruta chalepensis extract (RCE) on α-amylase activity, type 2 diabetes, and lipid profile induced by obesity.Methods: obesity was induced by a high-fat, high-fructose diet. Obese rats were given either RCEor acarbose daily by gastric gavage. Results:In a dosage-dependent manner, Ruta chalepensis extracts dramatically reduced pancreatic α-amylase activity in in vitro research.. RCE therapy in obese rats decreased blood glucose levels by 22% by decreasing the activities of intestinal, pancreatic, and blood α-amylase by 25, 22, and 27%, respectively and improved insulin sensitivity evidenced by oral glucose tolerance test (OGTT). Additionally, biochemical analysis and histological examination demonstrated that giving RCE to those with type 2 diabetes who had been exposed to HFFD corrected their lipid profiles and preserved their liver and kidney functions.Conclusion:This study shows that RCE is a beneficial functional food for diabetics due to its ability to control lipid profiles, blood glucose levels, and protect against liver and kidney toxicity. Keywords: Ruta chalepensis, type 2 diabetes, lipid profile, α-amylase Running title:Ruta chalepensis, diabetes and liver-kidney functions in obese rat